An in-depth study of the Fe-Se system at the nanoscale reveals remarkable results on the electrocatalytic oxygen evolution reaction - Singh, Dinesh; Ghalawat, Monika; Poddar, Pankaj (European Journal of Inorganic Chemistry, 2025)
A catalyst for an electrocatalytic oxygen evolution reaction (OER) is a key component of the large-scale storage of renewable energy through the conversion of water into oxygen and hydrogen. Iron-based selenide materials are currently being considered as potential options for electrocatalytic oxygen evolution reaction (OER) because of their, widespread availability, low cost, and outstanding performance. In this study, we employed a thermal decomposition method to synthesize all stable phases of the Fe-Se system, including Fe7Se8, Fe3Se4, FeSe2, and FeSe. Additionally, we slurry-coated these phases onto a three-dimensional (3D) nickel foam substrate. The prepared 3D electrodes of Fe7Se8, Fe3Se4, FeSe2, and FeSe exhibit remarkably low overpotentials of 270, 276, 299, and 289 mV at a current density of 50 mA/cm2 for OER. In addition, the catalytic activity for OER is also tested on glassy carbon electrodes to compare its performance with the Ni-foam 3D substrate. The Fe7Se8 phase in the Fe-Se system exhibits the highest catalytic activity towards OER on both substrates due to variations in the Fe2+/Fe3+ ratio and the presence of Fe vacancies (cation vacancies) within the crystal lattice. Moreover, a faradaic efficiency of 98 % was exhibited by Fe7Se8 for the oxygen evolution reaction (OER).
Keywords: Iron selenide system; OER electrocatalyst; Thermal decomposition method